The impact of education on personality: Evidence from a German high school reform - Sarah Dahmann; Silke Anger (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2014)
This paper investigates the short-term effects of a reduction in the length of high school on students' personality traits using a school reform carried out at the state level in Germany as a quasi-natural experiment. Starting in 2001, academic-track high school (Gymnasium) was reduced from nine to eight years in most of Germany's federal states, leaving the overall curriculum unchanged. This enabled students to obtain a university entrance qualification (Abitur ) after a total of only 12 rather than 13 years of schooling. We exploit the variation in the length of academic-track high school over time and across states to identify the effect of schooling on students' Big Five personality traits and on their locus of control. Using rich data on adolescents and young adults from the German Socio-Economic Panel (SOEP) study, our estimates show that shortening high school caused students on average to be more extroverted and less emotionally stable. Our estimates point to important heterogeneous effects. In addition to differences between East and West Germany, we find that male students and students from disrupted families showed stronger personality changes following the reform: they became more agreeable and more extroverted, respectively. We conclude that the educational system plays an important role in shaping adolescents' personality traits. – – Diese Studie untersucht die kurzfristigen Effekte der Verkürzung der Gymnasialzeit auf die Persönlichkeitsmerkmale von Schülern und verwendet dafür eine auf Bundeslandebene durchgeführte Schulreform als quasi-natürliches Experiment. Seit 2001 wurde in den meisten deutschen Bundesländern die Gymnasialzeit von neun auf acht Jahre unter Beibehaltung des Gesamtlehrplans reduziert. Dadurch konnten Abiturienten nach nur 12 anstatt 13 Schuljahren die Hochschulzugangsberechtigung erlangen. Wir nutzen die Variation in der Gymnasialdauer über die Zeit und zwischen Bundesländern, um den Effekt von Schule auf die "Big Five" Persönlichkeitsmerkmale und die Kontrollüberzeugung von Schülern zu identifizieren. Auf Basis umfangreicher Daten zu Jugendlichen und jungen Erwachsenen aus der Längsschnittstudie Sozio-oekonomisches Panel (SOEP) zeigen unsere Schätzergebnisse, dass die Verkürzung der Gymnasialdauer dazu geführt hat, dass Gymnasiasten durchschnittlich extrovertierter und weniger emotional stabil sind als vor der Reform. Unsere Schätzungen deuten auf wichtige heterogene Effekte hin: zusätzlich zu Unterschieden zwischen Ost- und Westdeutschland finden wir, dass männliche Schüler und Schüler aus nicht-intakten Familien stärkere Persönlichkeitsveränderungen nach der Reform aufweisen; sie wurden sozial verträglicher beziehungsweise extrovertierter. Wir schlussfolgern, dass das Bildungssystem eine bedeutende Rolle bei der Entwicklung der Persönlichkeitsmerkmale von Jugendlichen spielt.
Keywords: I21; I28; J24; 330; Non-cognitive Skills; Big Five; Locus of Control; Skill Formation; High School Reform